Analisis Metode Analytic Network Process pada Pemilihan Faktor Dominan Siswa Berprestasi di MTS Pembina - Warlinda, Iis; Windarto, Agus Perdana; Fauzan, M (STIKOM Tunas Bangsa Pematangsiantar, 2021)
School is a place for students to gain knowledge. Every school has a goal which is to improve the quality of the education world, as well as the MTS Pembina Maligas Bayu school. To realize this goal there must be improvements in service, teaching and assessment in order to make a quality school. In this case the homeroom teacher is faced with a problem that is the selection of high achieving students who fit the criteria desired by the school. The purpose of this study is to analyze which factors are the most dominant in determining student achievement. The selection of high achieving students has many factors and has different values, so we need an Analytic Network Process (ANP) method to overcome them. Analytic Network Process (ANP) methods including decision support system techniques, Analytic Network Process (ANP) is a mathematical theory that allows dealing with interrelated factors and feedback in a structured manner. The data of this study came from student questionnaires which had a rating of 1-10. With alternative morals (A1), Grades (A2), Discipline (A3), Absence (A4), The role of the teacher (A5). Whereas A1 0.16%, A2 0.02%, A3 0.02%, A4 0.07% and A5 0.06%. It is hoped that this research can provide input to the MTS Pembina schools to focus on the dominant factor in the selection of outstanding students so as to increase the number of outstanding students.